“I Want Her to Make Correct Decisions on Her Own:” Former Soviet Union Mothers' Beliefs about Autonomy Development - Komolova, Masha; Lipnitsky, Jane Y. (Frontiers in Psychology, 2018)
This qualitative study examined Former Soviet Union (FSU) mothers’ explicit and implicit attitudes and parenting practices around adolescents’ autonomy development. Interviews were conducted with ten mothers who had immigrated from the FSU to the US between 10 and 25 years ago, and who had daughters between the ages of 13 and 17 years. Mothers predominantly defined autonomy in terms of adolescents’ ability to carry out instrumental tasks, make correct decisions, and financially provide for themselves, but rarely mentioned psychological or emotional independence. Mothers reflected on the various aspects of autonomy emphasized in their country of origin and America, and balancing the two sets of cultural values in their parenting. Although mothers discussed attempts to adopt a less authoritarian approach to parenting than they themselves experienced as children, some mothers’ controlling attitudes were revealed through a close analysis of their language. The findings provide important insights into the parenting experiences of FSU immigrant mothers, and the way in which autonomy-related processes may vary cross-culturally. Implications for parenting and clinical practice are also discussed.